Memristive Devices: Analog–Digital Hybrid Memristive Devices for Image Pattern Recognition with Tunable Learning Accuracy and Speed (Small Methods 10/2019). Issue 10 (15th October 2019) - Lin, Ya; Wang, Cong; Ren, Yanyun; Wang, Zhongqiang; Xu, Haiyang; Zhao, Xiaoning; Ma, Jiangang; Liu, Yichun
Abstract : In article number1900160 by Zhongqiang Wang, Haiyang Xu and co‐workers, an Au/WO3−x /Ti memristive device is demonstrated that can exhibit hybrid analog and digital resistive switching behavior by relying on interface and bulk conductance modulation, respectively. Using a spike‐timing‐dependent plasticity learning scheme, an effective method is developed to tune learning accuracy and speed of pattern recognition by adjusting the proportion of analog to digital devices in the memristor crossbar array.